PEMBERDAYAAN MASYARAKAT BERBASIS EKONOMI SIRKULAR MELALUI PRODUKSI SABUN MINYAK JELANTAH - Sadiq Ardo Wibowo; Citra Indah Asmarawati; Maria Angela Valentine (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2026)
This community service program aims to increase environmental awareness and economic capacity in the community through training in the production of environmentally friendly soap from used cooking oil in Sagulung Village, Batam City. The main problems faced by the participants include the high volume of used cooking oil that is improperly disposed of in households and the community's low entrepreneurial skills. The program implementation method consists of preparation, socialization, pre-test, theoretical and practical training, and business mentoring for two months. Evaluation of the program's success was carried out using pre-test and post-test methods to measure improvements in participant understanding, observation of practical skills, and analysis of product quality and business feasibility. A total of 15 participants participated in this program. The evaluation results showed an increase in the average score of participants' understanding from 46 to 84, or an increase of 82%. In addition, 450 liters of used cooking oil were successfully processed into 530 bars of soap with a pH of 9–10 and a free alkali content of <0.1% based on simple product testing. The economic analysis showed a net profit of IDR 825,000 with a Break-Even Point (BEP) of 200 chocolate bars. The program also successfully established micro-enterprise clusters with an average monthly turnover of Rp 1,950,000. These results demonstrate the program's effectiveness in increasing community capacity while supporting waste management and sustainable economic development.